Answer :
Certainly! To solve the linear system using determinants, we will utilize Cramer's rule. Let's consider the given system of equations:
[tex]\[ \begin{array}{l} 2 x + 3 y = 6 \\ -8 x - 3 y = 12 \end{array} \][/tex]
We can represent this system in matrix form as [tex]\(AX = B\)[/tex].
Here, the coefficient matrix [tex]\(A\)[/tex] is:
[tex]\[ A = \begin{pmatrix} 2 & 3 \\ -8 & -3 \end{pmatrix} \][/tex]
The variables matrix [tex]\(X\)[/tex] is:
[tex]\[ X = \begin{pmatrix} x \\ y \end{pmatrix} \][/tex]
The constants matrix [tex]\(B\)[/tex] is:
[tex]\[ B = \begin{pmatrix} 6 \\ 12 \end{pmatrix} \][/tex]
### Step 1: Calculate the Determinant of Matrix [tex]\(A\)[/tex], denoted as [tex]\(|A|\)[/tex]:
[tex]\[ |A| = \begin{vmatrix} 2 & 3 \\ -8 & -3 \end{vmatrix} = (2 \times -3) - (3 \times -8) = -6 + 24 = 18 \][/tex]
Thus, [tex]\(|A| = 18\)[/tex].
### Step 2: Calculate the Determinant of Matrix [tex]\(A_x\)[/tex], denoted as [tex]\(|A_x|\)[/tex]:
Matrix [tex]\(A_x\)[/tex] is formed by replacing the first column of matrix [tex]\(A\)[/tex] with the constants from matrix [tex]\(B\)[/tex]:
[tex]\[ A_x = \begin{pmatrix} 6 & 3 \\ 12 & -3 \end{pmatrix} \][/tex]
[tex]\[ |A_x| = \begin{vmatrix} 6 & 3 \\ 12 & -3 \end{vmatrix} = (6 \times -3) - (3 \times 12) = -18 - 36 = -54 \][/tex]
Therefore, [tex]\(|A_x| = -54\)[/tex].
### Step 3: Calculate the Determinant of Matrix [tex]\(A_y\)[/tex], denoted as [tex]\(|A_y|\)[/tex]:
Matrix [tex]\(A_y\)[/tex] is formed by replacing the second column of matrix [tex]\(A\)[/tex] with the constants from matrix [tex]\(B\)[/tex]:
[tex]\[ A_y = \begin{pmatrix} 2 & 6 \\ -8 & 12 \end{pmatrix} \][/tex]
[tex]\[ |A_y| = \begin{vmatrix} 2 & 6 \\ -8 & 12 \end{vmatrix} = (2 \times 12) - (6 \times -8) = 24 + 48 = 72 \][/tex]
So, [tex]\(|A_y| = 72\)[/tex].
### Summary of Determinants:
[tex]\[ |A| = 18 \][/tex]
[tex]\[ |A_x| = -54 \][/tex]
[tex]\[ |A_y| = 72 \][/tex]
[tex]\[ \begin{array}{l} 2 x + 3 y = 6 \\ -8 x - 3 y = 12 \end{array} \][/tex]
We can represent this system in matrix form as [tex]\(AX = B\)[/tex].
Here, the coefficient matrix [tex]\(A\)[/tex] is:
[tex]\[ A = \begin{pmatrix} 2 & 3 \\ -8 & -3 \end{pmatrix} \][/tex]
The variables matrix [tex]\(X\)[/tex] is:
[tex]\[ X = \begin{pmatrix} x \\ y \end{pmatrix} \][/tex]
The constants matrix [tex]\(B\)[/tex] is:
[tex]\[ B = \begin{pmatrix} 6 \\ 12 \end{pmatrix} \][/tex]
### Step 1: Calculate the Determinant of Matrix [tex]\(A\)[/tex], denoted as [tex]\(|A|\)[/tex]:
[tex]\[ |A| = \begin{vmatrix} 2 & 3 \\ -8 & -3 \end{vmatrix} = (2 \times -3) - (3 \times -8) = -6 + 24 = 18 \][/tex]
Thus, [tex]\(|A| = 18\)[/tex].
### Step 2: Calculate the Determinant of Matrix [tex]\(A_x\)[/tex], denoted as [tex]\(|A_x|\)[/tex]:
Matrix [tex]\(A_x\)[/tex] is formed by replacing the first column of matrix [tex]\(A\)[/tex] with the constants from matrix [tex]\(B\)[/tex]:
[tex]\[ A_x = \begin{pmatrix} 6 & 3 \\ 12 & -3 \end{pmatrix} \][/tex]
[tex]\[ |A_x| = \begin{vmatrix} 6 & 3 \\ 12 & -3 \end{vmatrix} = (6 \times -3) - (3 \times 12) = -18 - 36 = -54 \][/tex]
Therefore, [tex]\(|A_x| = -54\)[/tex].
### Step 3: Calculate the Determinant of Matrix [tex]\(A_y\)[/tex], denoted as [tex]\(|A_y|\)[/tex]:
Matrix [tex]\(A_y\)[/tex] is formed by replacing the second column of matrix [tex]\(A\)[/tex] with the constants from matrix [tex]\(B\)[/tex]:
[tex]\[ A_y = \begin{pmatrix} 2 & 6 \\ -8 & 12 \end{pmatrix} \][/tex]
[tex]\[ |A_y| = \begin{vmatrix} 2 & 6 \\ -8 & 12 \end{vmatrix} = (2 \times 12) - (6 \times -8) = 24 + 48 = 72 \][/tex]
So, [tex]\(|A_y| = 72\)[/tex].
### Summary of Determinants:
[tex]\[ |A| = 18 \][/tex]
[tex]\[ |A_x| = -54 \][/tex]
[tex]\[ |A_y| = 72 \][/tex]